Wire-based directed energy deposition of NiTiTa shape memory alloys - Zuo, Xinde (2022)
Supporting for the Chinese Civil Aviation Administration (No. U1933129 ), Key Program of the Natural Science Foundation of Tianjin (No. 19JCZDJC39000 ). JPO acknowledges the Fundação para a Ciência e Tecnologia ( FCT ) for its support via the project UID/00667/2020 (UNIDEMI). LA/P/0037/2020, Publisher Copyright: © 2022 The Authors